Tumor epitope spreading by a novel multivalent therapeutic cellular vaccine targeting cancer antigens to invariant NKT-triggered dendritic cells in situ - Yamasaki, Satoru; Shimizu, Kanako; Fujii, Shin-ichiro (Frontiers in Immunology, 2024)
Cancer is categorized into two types based on the microenvironment: cold and hot tumors. The former is challenging to stimulate through immunity. The immunogenicity of cancer relies on the quality and quantity of cancer antigens, whether recognized by T cells or not. Successful cancer immunotherapy hinges on the cancer cell type, antigenicity and subsequent immune reactions. The T cell response is particularly crucial for secondary epitope spreading, although the factors affecting these mechanisms remain unknown. Prostate cancer often becomes resistant to standard therapy despite identifying several antigens, placing it among immunologically cold tumors. Consequently, we aim to leverage prostate cancer antigens to investigate the potential induction of epitope spreading in cold tumors. This study aimed to identify specific factors involved in secondary epitope spreading based on artificial adjuvant vector cell therapy, a method established as invariant natural killer T (iNKT) -licensed DC therapy. We concentrated on three prostate cancer antigens (prostate-specific membrane antigen (PSMA), prostate-specific antigen (PSA), and prostatic acid phosphatase (PAP)). We developed cellular cancer vaccines expressing these three antigens, loaded onto CD1d+ cells with iNKT cell ligands on their surface—referred to as multivalent aAVC for the prostate (aAVC-PROS). By introducing allogeneic cells with the antigen and murine CD1d mRNA, followed by α-galactosylceramide (α-GalCer) loading, we generated five types of aAVCs and four types of prostate antigen-expressing cold tumors. We evaluated iNKT activation and cytotoxic T cell (CTL) responses against tumor cells prompted by the aAVCs. First, our study revealed that one prostate antigen expressing-aAVC therapy primes T cells for primary tumor antigens and induces them to identify and target additional tumor antigens, triggering a tumor antigen-spreading response. Then, we investigated the immune response by aAVC-PROS. Our findings demonstrated that multiple antigen responsive CTLs had preventive and therapeutic effects against tumor progression upon iNKT cell activation. Additionally, we demonstrated that aAVC-PROS therapy elicits multiple antigen-specific T cells. Our results propose that multivalent antigen-expressing aAVCs present a promising therapeutic option and could be a more comprehensive therapy for treating cold tumors like prostate cancer.